Qari Selebriti: Resitasi Alquran dan Anak Muda Muslim Indonesia di Era Media Sosial - Nafisah, Lailiyatun (UIN Sunan Kalijaga Yogyakarta, 2021)
Imas Lu’ul Jannah, Qari Selebriti: Resitasi Alquran dan Anak Muda Muslim di Era Media Sosial (Yogyakarta: Pascasarjana UIN Sunan Kalijaga, 2021This book discusses the relationship between social media and Qur’anic recitation with the focus on the case study of the phenomena of the popularity of young celebrity Quranic reciters (qari) in Indonesia. This book conveys some findings: the emergence of the Qur’anic recitation in the public sphere of Indonesian social media cannot be separated from the advancement of the technology of social media in the Indonesian socio-political context. Second, Youtube and Instagram play the role not only as facilitating the observed reciters (Muzammil, Taqy, Boim, and Salim) in gaining popularity but also as a medium to set the Qur’an closer to its audiences. Third, the dakwa movement of these celebrity reciters has impacts, such as the shift of the Qur'anic sound from the sacred state to the secular culture of social media and the introduction of religious atmosphere in the digital world.